2019
DOI: 10.1161/jaha.119.012143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cardiovascular Disease Risk Factors in Childhood Glomerular Diseases

Abstract: Background Cardiovascular disease is a major cause of morbidity and mortality in children with chronic kidney disease. We sought to determine the prevalence of cardiovascular risk factors in children with glomerular disease and to describe current practice patterns regarding risk factor identification and management. Methods and Results Seven‐hundred sixty‐one children aged 0 to 17 years with any of 4 biopsy‐confirmed primary glomerular diseases (minimal change disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Cardiovascular disorders (CVDs) remain the leading cause of death worldwide, with very high incidence and mortality rates (Ashoor et al, 2019). Oxidative stress is known to be a key player in the development of coronary heart disease and has been well described as the mechanism driving a range of health conditions, such as hypertension, dyslipidemia, metabolic syndrome, diabetes mellitus, and obesity (Pignatelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disorders (CVDs) remain the leading cause of death worldwide, with very high incidence and mortality rates (Ashoor et al, 2019). Oxidative stress is known to be a key player in the development of coronary heart disease and has been well described as the mechanism driving a range of health conditions, such as hypertension, dyslipidemia, metabolic syndrome, diabetes mellitus, and obesity (Pignatelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lipid alterations in different renal pathological types might differ. Hypercholesterolemia was the most frequent complication in IMN (82%) among four common primary glomerular diseases including membranous nephropathy, IgA nephropathy, minimal change disease and FSGS [ 10 ]. In addition, our result indicated non-HDL-C as the most relevant marker among other markers in the lipid profile with proteinuria in IMN.…”
Section: Discussionmentioning
confidence: 99%
“…The linkage between hypercholesterolemia and outcomes of primary glomerular diseases has been reported [ 10 ]. In a multicenter cohort study involving 761 children, 72% of participants not in remission had hypercholesterolemia than 43% of those in remission ( P < 0.001), indicating an association between hypercholesterolemia and not achieving remission [ 10 ]. The effect of lipid profile parameters on IMN has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Another single-center study found that BMI was not related to progression of kidney disease [16]. Further, although the prevalence of obesity in patients with glomerular disease has been reported in a handful of studies [17][18][19], the association between obesity and cardiovascular risk profile has not been previously described.…”
Section: Introductionmentioning
confidence: 97%